Antimicrobial Activity of Intraurethrally Administered Probiotic Lactobacillus casei in a Murine Model of Escherichia coli Urinary Tract Infection - Asahara, Takashi (American Society for Microbiology, 2001)
The antimicrobial activity of the intraurethrally administered probiotic Lactobacillus casei strain Shirota against Escherichia coli in a murine urinary tract infection (UTI) model was examined. UTI was induced by intraurethral administration of Escherichia coli strain HU-1 (a clinical isolate from a UTI patient, positive for type 1 and P fimbriae), at a dose of 1 × 10(6) to 2 × 10(6) CFU in 20 μl of saline, into a C3H/HeN mouse bladder which had been traumatized with 0.1 N HCl followed immediately by neutralization with 0.1 N NaOH 24 h before the challenge infection. Chronic infection with the pathogen at 10(6) CFU in the urinary tract (bladder and kidneys) was maintained for more than 3 weeks after the challenge, and the number of polymorphonuclear leukocytes and myeloperoxidase activity in the urine were markedly elevated during the infection period. A single administration of L. casei Shirota at a dose of 10(8) CFU 24 h before the challenge infection dramatically inhibited E. coli growth and inflammatory responses in the urinary tract. Multiple daily treatments with L. casei Shirota during the postinfection period also showed antimicrobial activity in this UTI model. A heat-killed preparation of L. casei Shirota exerted significant antimicrobial effects not only with a single pretreatment (100 μg/mouse) but also with multiple daily treatments during the postinfection period. The other Lactobacillus strains tested, i.e., L. fermentum ATCC 14931(T), L. jensenii ATCC 25258(T), L. plantarum ATCC 14917(T), and L. reuteri JCM 1112(T), had no significant antimicrobial activity. Taken together, these results suggest that the probiotic L. casei strain Shirota is a potent therapeutic agent for UTI.